Sera from breakthrough infections with SARS-CoV-2 BA.5 or BF.7 showed lower neutralization activity against XBB.1.5 and CH.1.1 - Shuo Liu; Ziteng Liang; Jianhui Nie; Wei bo Gao; Xinyi Li; Li Zhang; Yuanling Yu; Youchun Wang; Weijin Huang (Emerging Microbes and Infections, 2023)
From December 2022 to January 2023, SARS-CoV-2 infections caused by BA.5 and BF.7 subvariants of B.1.1.529 (Omicron) spread in China. It is urgently needed to evaluate the protective immune responses in the infected individuals against the current circulating variants to predict the future potential infection waves, such as the BQ.1.1, XBB.1.5, and CH1.1 variants. In this study, we constructed a panel of pseudotyped viruses for SARS-CoV-2 for the past and current circulating variants, including D614G, Delta, BA.1, BA.5, BF.7, BQ.1.1, XBB.1.5 and CH.1.1. We investigated the neutralization sensitivity of these pseudotyped viruses to sera from individuals who had BA.5 or BF.7 breakthrough infections in the infection wave of last December in China. The mean neutralization ID50 against infected variants BA.5 and BF.7 are 533 and 444, respectively. The highest neutralizing antibody level was observed when tested against the D614G strain, with the ID50 of 742, which is about 1.52-folds higher than that against the BA.5/BF.7 variant. The ID50 for BA.1, Delta, and BQ.1.1 pseudotyped viruses were about 2–3 folds lower when compared to BA.5/BF.7. The neutralization activities of these serum samples against XBB.1.5 and CH.1.1 decreased 7.39-folds and 15.25-folds when compared to that against BA.5/BF.7. The immune escape capacity of these two variants might predict new infection waves in future when the neutralizing antibody levels decrease furtherly.